From Fraudsters to Scammers and Cyber-Villains, Tech-Savvy Criminals Are Out to Steal Your Money - Metts, Stephanie; Bressler, Martin S. (Journal of Accounting and Finance, 2023)
Today, more than ever before, criminals are out to steal from your business. However, today, criminals not only use organized shoplifting gangs and engage in armed robberies, but they now also use computers and the internet. Bernie Madoff and Sam Bankman-Fried have joined the lengthy list of well-known criminals before Charles Ponzi. The Fraud Triangle (Cressey, 1973) is based upon Opportunity, Incentive, and Rationalization. The COVID-19 pandemic created a perfect storm of opportunity for would-be scammers. The federal government fueled opportunity with $800 billion in COVID relief funding for the Paycheck Protection Program and up to $400 billion for COVID unemployment relief. According to the Association of Certified Fraud Examiners (ACFE) small businesses are often targeted as they tend to have fewer safeguards in place to prevent fraud. The ACFE reports that the average loss for a small business fraud is $100,000 and an average of five percent of annual revenue. In this paper, the authors provide an overview of current fraud activities and a study of the Traits of Sympathy survey to help examine whether a relationship exists between one’s rationalization and sympathy in their decision to commit fraud in the pre-fraud state. We present research findings and offer recommendations.